Analisis Pengaruh Pertumbuhan Ekonomi, Upah MinimumDan Pengangguran Terhadap Tingkat KonsumsiMasyarakat Di Provinsi Jawa TengahTahun 2007-2015 - Puspitasari, Sandra Dewi; , Dr. Didit Purnomo, S.E, M.Si (2017)
This research aims to analyze the influence of shopping areas, the inflation rate, the number of poor and unemployed against the IPM in Central Java province in 2012-2014. This type of research is a composite time series (in order of time) and cross section. Types of data used are secondary data with panel data type. The sample in this research is the 35 counties. Data analysis techniques used in this research is the regression of the panel. the selection of the most appropriate model of diipilih in this research is the Random Effect Method (REM). REM models have power ramal high enough. Based on the test results of F, simultaneous variable GDP, minimum wage,unemployment and the effect on the consumption rate in the province of Central Java in 2007-2015. Determinant of the coefficients of test results (R2) showed that the magnitude of R-square value is 0.837771 or of 83,77 persen. This means that the variation of the consumption rate can be explained by the independent variable that is in statistical models such as GDP, minimum wage, and unemployment . While the rest of 16,23 persen explained by other factors that are not included in the model. Based on a test of the validity of the influence (t-test) on significance (α) of 0.05, GDP and variable consumpt have influence positioni significantly,the unemployment has no influence on consumption, while the minimum wage variable have influence position and significance on consumption rate in the province Central Java in 2007-2015.